ARTERIAL STIFFNESS IS ASSOCIATED WITH A PROTHROMBOTIC STATE IN NON-DIABETIC ESSENTIAL HYPERTENSIVE PATIENTS. (April 2021) - Bulfone, Luca; Catena, Cristiana; Da Porto, Andrea; Colussi, Gianluca; Frangipane, Alessandro; Duratti, Andrea; Cavarape, Alessandro; Sechi, Leonardo A.
Abstract : Objective: Previous studies reported that a prothrombotic state is associated with early subclinic damage in arterial hypertension. Arterial stiffening can be estimated by measurement of the pulse wave velocity (cfPWV) and the augmentation index (AIx) and predicts cardiovascular events in general population and in hypertension. Previous assessments of the impact of the coagulative system on arterial stiffness reported inconsistent results. We examined the relationships among the AIx and cfPWV, and hemostatic system, in non-diabetic essential hypertensive (EH) patients. Design and method: In 147 EH subjects (age 52 ± 13 years, 72 men) we evaluated clinical characteristics, renal function, plasma levels of glucose, lipids, fibrinogen, D-dimer, plasminogen activator inhibitor-1 (PAI-1), tissue-plasminogen activator (t-PA), prothrombin fragment 1+2 (F1+2), von Willebrand Factor antigen (vWF Ag), antithrombin III (ATIII), coagulation C and S proteins, and we measured the AIx and cfPWV. Results: At univariate analysis the AIx was significantly and directly related to fibrinogen (r = 0.300, P < 0.001), D-dimer (r = 0.277, P = 0.001) and PAI-1 (r = 0.268, P = 0.009). The cfPWV was significantly and directly related to fibrinogen (r = 0.273, P = 0.001), D-dimer (r = 0.285, P < 0.001), F1+2 (r = 0.267, P = 0.014) and PAI-1 (r = 0.368, P < 0.001). At multivariate analysis AIx was independently associated with levels of fibrinogen (B = 0.224, P = 0.004), D-dimer (B = 0.170, P = 0.037) and PAI-1 (B = 0.341, P = 0.001), and cfPWV was independently associated with levels of D-dimer (B = 0.207, P = 0.005) and PAI-1 (B = 0.208, P = 0.048). Logistic regression indicated that AIx above the median value was significantly associated with levels of D-dimer and PAI-1. Conclusions: In non-diabetic patients with EH, arterial stiffening is associated with evidence of a prothrombotic state suggesting that measurement of some hemostatic variables might be useful to identify subjects at increased risk of vascular damage.